Solid-State Lasers A Graduate Text - Koechner, Walter. (Advanced Texts in Physics,, 2003)
Solid-state lasers have seen a fast and steady development and are the ubiquitous tool both for research and industrial applications. The author's monograph Solid-State Lasers has become the most-used reference book in this area. The present graduate text on solid-state lasers takes advantage of this rich source by focusing on the needs at the graduate level and those who need an introduction. Numerous exercises with hints for solution, new text and updated material where needed make this text very accessible.